Logistics in the Development Strategy of the City – Transportation Aspect of Municipal Waste - Gradowicz, Cezary (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Processing must update on the existing urban development strategy, dictated by considerations of sustainable development, with the need to consider the design standards. Article presents the concept of logistics planning as part of the coordination of sub-targets of this strategy. Specifically relates to the issue logistics processes in municipal waste management subsystem.